Water Security Index of the Municipality of São Paulo/SP: strategic indicator of urban resilience - Negreiros, Meire Vidal de; Rocha, Paulo César (Technical and Scientific Journal Green Cities, 2025)
Objective - To analyze the Water Security Index (ISH) of the municipality of São Paulo, SP, focusing on the human, economic, ecosystem, and resilience dimensions, and urban resilience. Methodology - The research is qualitative and quantitative in nature, with a literature review based on documents and technical reports, water resources, water security, sanitation, and river basin plans, and information on water resources and sanitation systems. Regarding the Water Security Index (ISH) of the municipality of São Paulo, SP, focusing on the human, economic, ecosystem, and resilience dimensions, and demonstrating that this index is an important indicator of urban resilience. Originality/Relevance – The academic relevance of the topic suggests new research to be added to the composition of the water security index, such as: inclusion of water loss indicators with reduction targets, per capita water consumption in relation to average water availability, and the inclusion of minimum, average, and maximum temperatures to assess climate trends. Results – The analysis of the Water Security Index of the Municipality of São Paulo demonstrates its importance for urban resilience, given that 84% of the flows allocated in the Alto Tietê Basin, including the Municipality of São Paulo, are allocated to urban supply. Furthermore, the Basin has per capita water consumption in relation to its average water availability, at 128.79 m³/inhab.year, well below the critical value defined by the United Nations (UN), less than 1,500 m³/inhab.year. Furthermore, it is suggested to intensify the use of artificial intelligence for flow forecasting. Theoretical/Methodological Contributions – the research suggests expanding the indicators of the methodology applied to the water security index, as indicated by academic relevance. Social and Environmental Contributions – the study suggests actions that promote the conservation of water resources in quantitative and qualitative terms, especially for the continuity of urban water supply, as well as other uses, in addition to the survival of natural and artificial ecosystems.